The evaluation of comprehensive medication management for chronic diseases in primary care clinics, a Texas delivery system reform incentive payment program - Tong Han Chung; Ricardo J. Hernandez; Anaelle Libaud-Moal; Linh K. Nguyen; Lincy S. Lal; J. Michael Swint; Pio Juan Lansangan; Yen-Chi L. Le (BMC, 2020)
Abstract Background The Institute of Medicine reported that more than 1.5 million preventable adverse drug events occur annually in the United States. Comprehensive Medication Management (CMM) is the medication review process to improve clinical outcomes, enhance patient adherence, reduce drug therapy problems and reduce health care costs. University of Texas (UT) Physicians implemented a CMM program in several community-based clinics. We evaluated the effectiveness of CMM to reduce drug therapy problems and achieve medical cost savings. Methods This was a retrospective, observational study of CMM participants from October 2015 to September 2016. Program participants included patients aged 18 years or older who had taken more than 4 prescribed medications and were diagnosed with at least one of the following chronic diseases: hypertension, congestive heart failure, chronic obstructive pulmonary disease, asthma or diabetes. Under the CMM program, a clinical pharmacist reviewed patients' electronic health records and created action plans to resolve identified drug problems. As part of the evaluation of the clinical process, two independent physicians conducted peer review on the recommendations issued by the pharmacist in order to establish inter-rater reliability of drug therapy problems and potential consequent medical services. The drug therapy problems were identified and classified into four categories: indication, effectiveness, safety and/or compliance. The average cost of avoided medical services was obtained based on cost extrapolations from the literature, combined with hospital discharge data. Potential medical services avoided were linked to the average cost of those services to calculate the total cost savings of the program from the payers' perspective. Results By reviewing electronic health records of 3280 patients, the pharmacist identified 301 drug therapy problems and resolved 49.8% of these problems with collaboration from the patient's primary care physician or care team. The most commonly identified drug problems were related to potentially adverse drug reactions or inappropriate drug dosage. The CMM program resulted in potential cost savings of $1,143,015. Conclusions The CMM program resolved medication therapy problems among program participants and achieved significant health care cost savings.